Analisa dan Rancangan Sistem Penjualan Bahan Material dan Konstruksi Berbasis Web pada CV. Tri Jaya Konstruksi - Afriyanto; Andi Afif Nawawi; Nanang Selamet Riyadi; Nurohman; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
CV. Tri Jaya Konstruksi is a trading company that provides construction materials such as steel plates, iron pipes, sand, cement, and other building tools. For now, the recording of incoming stock and sales on CV. Tri Jaya Konstruksi is still being carried out manually, so it can cause several problems, such as errors in the data recording process and loss of sales records or notes. These various things make the company's performance less efficient with respect to manpower and the time spent recording and searching for data on goods and transactions that are large in number. Therefore, we try to analyze and design a computerized sales system so that it can be the best solution for the problems faced by CV. Tri Jaya Konstruksi. The method we use is the waterfall method, which consists of five phases: analysis, design, implementation, testing, and maintenance. The system that we propose is designed using a MySQL database, PHP programming language, HTML, CSS, Javascript, and Bootstrap. Through the analysis and design of materials and construction sales systems at CV. Tri Jaya Konstruksi, companies can apply it to build information systems that make it easier for users and employees to find information, increase business efficiency, and prioritize integrated and programmed transactions to build better relationships with customers.